Os Kaingang e a Usina Hidrelétrica do Apucaraninha (Revista de História Regional, 2021)
The current Apucaraninha Indigenous Land, located in Tamarana (PR), has an area of 5,574 hectares and a population of 1,700 Kaingang Indigenous people. In this territory is located the Apucaraninha Hydroelectric Power Plant, which was built in 1946 by the Electric Company Londrina S/A (EELSA), responsible for supplying electricity to the region of Londrina until 1974, when it was expropriated by the Paranaense Energy Company (COPEL). Through documentary analysis and field research, consisted of oral interviews, this paper aims to understand the socio-historical relations established between the Kaingang, and the representatives of the indigenous body, and EELSA. The actions of the indigenous ensured the demarcation of the area as an indigenous territory and the relations with the company's employees aroused in the Kaingang the feeling of ownership of the plant, motivating their claims and negotiations with the COPEL.